Details of the vedibandha and jangha - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha shows the vedibandha and jangha on its vertical axis. The vedibandha comprises various mouldings such as pitha, kapotapailka, karnika, grassapatta, manibandha, gaggarika, kumbha and kalasha. The jangha has a bhadra and karna and a horizontal band at the center runs across the wall.